Automatic new word acquisition: spelling from acoustics - Alleva, Fil; Lee, Kai-Fu (HLT '89 Proceedings of the workshop on Speech and Natural Language, 1989)
The problem of extending the lexicon of words in an automatic speech recognition system is commonly referred to as the new word problem. When encountered in the context of an embedded speech recognition system this problem can be be divided into the following sub-problems. First, identify the presence of a new word. Second, acquire a phonetic transcription of the new word. Third, acquire the orthographic transcription (spelling) of the new word. In this paper we present the results of a preliminary study that employs a novel approach to the problem of acquiring the orthographic transcription through the use of an n-gram language model of english spelling and a quad-letter labeling of acoustic models that when taken together potentially produce an acoustic to spelling transcription of any spoken input.